Dye Removal from Aqueous Solution by Using Chemical Treated Sugarcane Bagasse at Various pH - Saiful Azhar, Saad; Azlinda, Abdul Ghani; Suhardy, Daud; Farizul Hafiz, Kasim; Mohd Nazry, Salleh (Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 2008)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 9th - 10th December 2006 at Putra Palace Hotel, Kangar, Perlis.